2022
DOI: 10.1111/apt.17046
|View full text |Cite
|
Sign up to set email alerts
|

Review article: vascular effects of PPARs in the context of NASH

Abstract: Summary Background Peroxisome proliferator‐activated receptors (PPARs) are ligand‐activated transcription factors known to regulate glucose and fatty acid metabolism, inflammation, endothelial function and fibrosis. PPAR isoforms have been extensively studied in metabolic diseases, including type 2 diabetes and cardiovascular diseases. Recent data extend the key role of PPARs to liver diseases coursing with vascular dysfunction, including nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 151 publications
0
3
0
Order By: Relevance
“…Peroxisome proliferator activated receptors (PPARs) are ligand-activated transcriptional factors, which belong to the nuclear receptor superfamily and play key roles in lipid and glucose metabolism [1][2][3][4]. Humans have three subtypes of PPARs: PPARα, PPARδ (also named as PPARβ), and PPARγ.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator activated receptors (PPARs) are ligand-activated transcriptional factors, which belong to the nuclear receptor superfamily and play key roles in lipid and glucose metabolism [1][2][3][4]. Humans have three subtypes of PPARs: PPARα, PPARδ (also named as PPARβ), and PPARγ.…”
Section: Introductionmentioning
confidence: 99%
“…[105][106][107] Recent data extend the key role of PPARs to liver diseases occurring with vascular dysfunction, including NAFLD. 108 PPAR-gamma is expressed in many tissues but its splicing isoform (PPAR-gamma2) is expressed solely in adipocytes and PPARgamma activation increases the production of adiponectin from adipocytes 109 that is an adipokine protein with insulin-sensitizing and anti-inflammatory effects.…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…Notably, Guixé-Muntet et al showed that the pharmacotherapy by targeting specific PPARs through modulating vascular effects provides novel insights into the treatment of nonalcoholic steatohepatitis-related CVD, including endothelial dysfunction, coagulation, inflammation, and vascular remodeling. 5 In addition, further research into the assessment of NAFLD-related CVD using a panel of PPAR-targeted biomarkers is possible, such as apolipoprotein B, interleukins 8 and 10, sterol regulatory element binding protein-1c, and tumor necrosis factor-alpha. 6 Thus, the investigation of pemafibrate in alleviating NAFLD-related CVD through specific biomarkers should be considered.…”
mentioning
confidence: 99%